2018
DOI: 10.1002/erv.2630
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome among young adult patients with anorexia nervosa in a randomised controlled trial

Abstract: Bulimic symptoms and the ability to identify and cope with emotional states appear to be important aspects that should be addressed in the treatment of young adult patients with AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…In addition, it moderated treatment effects: subjects with weaker BPD benefited more from a therapy centred on ED symptomatology (i.e., enhanced cognitive behaviour therapy for EDs, focused version, CBT‐Ef; see Thompson‐Brenner et al, 2016, for further details), while subjects with stronger BPD benefited more from a therapy including modules on interpersonal problems and mood intolerance (i.e., enhanced cognitive behaviour therapy for EDs, broad version, CBT‐Eb; see Thompson‐Brenner et al, 2016, for further details). The other five studies (Accurso et al, 2016; Castellini et al, 2012; Haynos et al, 2017; Nyman‐Carlsson et al, 2019; Zander, 2016) were not strictly focused on PD; rather, they focused on personality dimensions in a broader sense (see below, from personality subtypes to self‐directedness).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it moderated treatment effects: subjects with weaker BPD benefited more from a therapy centred on ED symptomatology (i.e., enhanced cognitive behaviour therapy for EDs, focused version, CBT‐Ef; see Thompson‐Brenner et al, 2016, for further details), while subjects with stronger BPD benefited more from a therapy including modules on interpersonal problems and mood intolerance (i.e., enhanced cognitive behaviour therapy for EDs, broad version, CBT‐Eb; see Thompson‐Brenner et al, 2016, for further details). The other five studies (Accurso et al, 2016; Castellini et al, 2012; Haynos et al, 2017; Nyman‐Carlsson et al, 2019; Zander, 2016) were not strictly focused on PD; rather, they focused on personality dimensions in a broader sense (see below, from personality subtypes to self‐directedness).…”
Section: Resultsmentioning
confidence: 99%
“…Another study (Nyman-Carlsson et al, 2019), instead, indicated that a high emotion dysregulation significantly predicted adverse outcomes.…”
Section: Emotion Dysregulationmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to cognitive and personality characteristics of AN patients [16,41], they are often unwilling to receive treatment themselves. Even if they receive treatment and successfully regain their weight over the course of treatment, they may not make significant improvement in cognitive symptoms and may relapse within a period of time after stopping treatment [42]. CBT has been found to be Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this lack of difference between treatments in keeping with the common factors view described earlier in the chapter, the study is underpowered and thus conclusions about common versus specific factors cannot be drawn. Predictors of outcome were reported in a separate study (Nyman-Carlsson et al, 2019). In the family therapy group, lower interoceptive deficits predicted higher weight gain, whilst bulimic behaviour and emotion dysregulation predicted increased scores on a diagnostic index comprised of questions relating to fear of weight gain, body image and eating habits.…”
Section: Discussionmentioning
confidence: 99%